Epidemiological Pattern of Renal Insufficiency among the Patients of Nephrology Unit of Dhaka Medical College Hospital, Dhaka, Bangladesh - Haq, Md Nazmul; Raaman, Latifur; Miah, Md Zohirul Islam; Gazi, Easin Ali; Baroi, Shukti Catherine (Faridpur Medical College Journal, 2014)
A hospital based descriptive cross sectional study was conducted at Nephrology unit of Dhaka Medical College Hospital (DMCH) to see the association between epidemiological pattern of renal insufficiency with sociodemographic factors, kidney related factors and others factors. Sources of data include patient interviews, diagnosis cards and case records. Respondents were categorized to their CKD stage according to their estimated GFR on Modification of Diet in Renal Disease (MDRD). The sample comprised 150 patients suffering from CKD with male and female ratio being 1.5:1, mean age of the population was 47 years (SD ± 14.5), 47.3% of the respondents had history of streptococcal throat infection and 10% had previous kidney disease Renal Replacement Therapy (RRT) was the commonly advised therapy for CKD indicating very late diagnosis of CKD. Total 49.3% had smoking habit while 60.7% was on regular physical exercise and 49.3% took extra salt on their dietary habit, 52.7% were diabetic and 78.7% were hypertensive and 40% had both diabetes and hypertension. Total 76.6% were in stage-5 of CKD where 60.7% of them used NSAID with 54.0% within normal range of BMI. There is statistically significant difference with stage of renal insufficiency and history of streptococcal throat infection (p=0.00) and therapy advised for CKD (P-0.01). Worldwide, CKD is becoming a common disease in the general population. It requires early, accurate and improved detction and mangemnt of diabetes and hypertension, the major contributors to CKD. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20391 Faridpur Med. Coll. J. 2013;8(2): 80-84